Impacts of COVID-19 on World Economy and Sustainable Development Goal in Nepal - Baniya, Binod; Ghimire, Ambika; Mahat, Anjal (Cognition, 2021)
COVID-19 has multifaceted impacts in economic and development sectors. Major economic impacts have raised the problem to meet the sustainable development goals in Nepal. In boarder scales, pandemic has affected to the national and international target of Sustainable Development Goals (SDGs). In this context, we have investigated the impacts of COVID-19 on different economic sectors and sustainable development goals in Nepal. The investigation was conducted using journal articles, government documents, policy reports, and conference papers, national and WHO situation reports, World Bank analysis data, COVID-19 web portals and UN sites of SDGs were reviewed. The study found that pandemic has triggered the most severe economic crisis in the world. The global output was declined, global trade are shrunk, labour markets (working hours, job losses and prosecuted shutdown of business) were seriously affected. The global GDP has declined and global economic recession has found extreme. This shrink in economics is expected to reverse global years of progress toward development goals and could force people back into extreme poverty. In Nepal, economic impacts of COVID-19 have made unable to meet the SDGs target to 2030. The economic road map of SDGs such as no poverty, zero hunger, economic growth are negatively affected. However, vaccination campaigns with international collaboration can lead positive economic influences in Nepal.